Muscle spindle and fusimotor activity in locomotion. Issue 2 (5th June 2015) - Ellaway, Peter H.; Taylor, Anthony; Durbaba, Rade
Abstract Mammals may exhibit different forms of locomotion even within a species. A particular form of locomotion (e.g. walk, run, bound) appears to be selected by supraspinal commands, but the precise pattern, i.e. phasing of limbs and muscles, is generated within the spinal cord by so‐called central pattern generators. Peripheral sense organs, particularly the muscle spindle, play a crucial role in modulating the central pattern generator output. In turn, the feedback from muscle spindles is itself modulated by static and dynamic fusimotor (gamma) neurons. The activity of muscle spindle afferents and fusimotor neurons during locomotion in the cat is reviewed here. There is evidence for some alpha–gamma co‐activation during locomotion involving static gamma motoneurons. However, both static and dynamic gamma motoneurons show patterns of modulation that are distinct from alpha motoneuron activity. It has been proposed that static gamma activity may drive muscle spindle secondary endings to signal the intended movement to the central nervous system. Dynamic gamma motoneuron drive appears to prime muscle spindle primary endings to signal transitions in phase of the locomotor cycle. These findings come largely from reduced animal preparations (decerebrate) and require confirmation in freely moving intact animals.